Stationary Solutions to the Three-Dimensional Compressible Nonisothermal Nematic Liquid Crystal Flows - Wanchen Cui; Hong Cai (Advances in Mathematical Physics, 2022)
In this paper, we study the stationary compressible nonisothermal nematic liquid crystal flows affected by the external force of general form in three-dimensional space. By using the contraction mapping principle, we prove the existence and uniqueness of strong solution around the constant state in some suitable function space.